Kemampuan Menulis Gelar Melalui Model Pembelajaran Cooperative dengan Tipe Talking Stick di Kelas IV SDN 101927 Sekip - Sari, Dwi Ratna; Harahap, Syarifah Ainun; Putri, Nizmi (Medan Resource Center, 2024)
This study aims to examine the effect of the cooperative learning model Talking Stick on the learning independence of fourth-grade students at SDN 101927 Sekip. The research employed an experimental method with a pretest-posttest control group design. The findings revealed that the Talking Stick cooperative learning model significantly influenced students' learning independence. The average independence score in the experimental class utilizing the Talking Stick model was 82.2, with a standard deviation of 9.06, compared to the control class employing conventional methods, which recorded an average independence score of 51.67 and a standard deviation of 7.18. Hypothesis testing showed a calculated t-value of 0.06, which was compared to the critical t-value at a 5% significance level (0.245). The results confirmed that the hypothesis was accepted, indicating that the Talking Stick learning model effectively enhances students' learning independence. This study underscores the importance of implementing cooperative learning strategies to foster students' autonomy and engagement in the learning process.